The neurobehavioral mechanisms of motivational control in attention-deficit/hyperactivity disorder. (June 2020) - Ceceli, Ahmet O.; Natsheh, Joman Y.; Cruz, Daniel; Tricomi, Elizabeth
Abstract: Attention-deficit/hyperactivity disorder (ADHD) poses debilitating impairments in the neurobehavioral systems governing reward-related processes—key to the control of motivated behaviors. Individuals with ADHD may rely on a motivational control system that favors cue-driven habits—rooted in the posterior putamen—over caudate and prefrontal cortex-driven goal-directed behaviors. We examined the neurobehavioral correlates of motivational control in ADHD. Twenty-five adults with ADHD and 25 neurotypicals underwent fMRI while training on two stimulus–response–outcome associations. A devaluation procedure followed, whereby they were selectively satiated on one of the snack outcomes, decreasing its value. A subsequent extinction test determined outcome-sensitivity (i.e., whether responses towards devalued snack diminished). Despite behavioral similarities, the ADHD group displayed a distinct neural signature marked by enhanced posterior putamen activation as a function of training. This region also displayed diminished functional connectivity with the dorsal anterior cingulate cortex, which is associated with top-down control. Our whole-brain analysis yielded ADHD-specific posterior putamen and opercular/insular cortex activity over the course of training—regions associated with stimulus-sensitivity and maladaptively rigid behaviors, respectively. Neural comparisons also identified hyper-recruitment of the hippocampus in the ADHD group. These results highlight corticostriatal discrepancies in ADHD, possibly serving as a biomarker of the disorder.